2020
DOI: 10.1002/dev.21951
|View full text |Cite
|
Sign up to set email alerts
|

Associations between empathy, inhibitory control, and physical aggression in toddlerhood

Abstract: Impaired empathy has been associated with aggression in children, adolescents and adults, but results have been contradictory for the preschool period. Impaired inhibitory control also increases the risk of aggression, and possibly moderates empathy‐aggression associations. The current study investigated whether empathy and inhibitory control are associated with aggression in toddlerhood. Furthermore, we aimed to clarify the role of inhibitory control in empathy and aggression, specifically, whether inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Conversely, weaker empathy is thought to entail a risk of inappropriate social behaviors, displayed through aggressivity and conflict, for example (Dahmen et al, 2004). Most studies have emphasized that empathy is negatively related to externalizing problems at an early age (Noten et al, 2020), preschool age (Strayer and Roberts, 2004;Ekerim-Akbulut et al, 2020), and school age (Deschamps et al, 2015(Deschamps et al, , 2018Malcolm-Smith et al, 2015), and in adolescence (LeSure-Lester, 2000;Lovett and Sheffield, 2007;Pouw et al, 2013). Feeling the same emotion as others discourages children from acting inappropriately, for example by hitting or mocking them (Hastings et al, 2000).…”
Section: Empathy Prosocial and Social Behaviors Externalizing And Internalizing Problemsmentioning
confidence: 99%
“…Conversely, weaker empathy is thought to entail a risk of inappropriate social behaviors, displayed through aggressivity and conflict, for example (Dahmen et al, 2004). Most studies have emphasized that empathy is negatively related to externalizing problems at an early age (Noten et al, 2020), preschool age (Strayer and Roberts, 2004;Ekerim-Akbulut et al, 2020), and school age (Deschamps et al, 2015(Deschamps et al, , 2018Malcolm-Smith et al, 2015), and in adolescence (LeSure-Lester, 2000;Lovett and Sheffield, 2007;Pouw et al, 2013). Feeling the same emotion as others discourages children from acting inappropriately, for example by hitting or mocking them (Hastings et al, 2000).…”
Section: Empathy Prosocial and Social Behaviors Externalizing And Internalizing Problemsmentioning
confidence: 99%
“…Although it is widely accepted that the relationship between empathy and ASB is simply the converse of the empathy-prosocial behavior relationship (Gery et al, 2009;Jolliffe & Farrington, 2004;Lovett & Sheffield, 2007), some interesting derivations have been noted. In line with expectation, some research has noted that empathy is negatively related to aggression and disruptive behavior (Bons et al, 2013;Miller & Eisenberg, 1988;Tampke et al, 2020;van Langen et al, 2014), children and adolescents with CDs had significantly lower empathy than those in the control group (e.g., de Wied et al, 2005;Kostić et al, 2016), but others have not found evidence that those who act antisocially have lower empathy (e.g., Noten et al, 2020). The explanation of these apparent contradictory findings, concerning Geng et al ( 2012), "appears to be related to both the seriousness of the ASB and whether cognitive or affective empathy was assessed" (p. 501).…”
mentioning
confidence: 79%
“…Empirical evidence bears out this supposition. Relational aggression is associated with greater cognitive functioning, and physical aggression with cognitive impairments (Noten et al, 2020; Poland et al, 2016). For instance, children with greater disinhibition may show more physical aggression (Baker et al, 2016; Ostrov et al, 2013; Poland et al, 2016), although this is not true for all children (Suurland et al, 2016).…”
Section: Icmentioning
confidence: 99%